The Effect of Interactive Multimedia Based Learning on Students' Mathematical Communication Ability - Lilis Marina Angraini; Vivin Anggraini Hardi (Jurnal Paedagogy, 2023)
This research aims to improve students' mathematical communication ability through interactive multimedia-based teaching materials to support the smooth running of learning activities, especially in online learning. The method used in this research is experimental, with the research design being a quasi-experimental nonequivalent control group carried out at two universities, Universitas Islam Riau (UIR) and Universitas Pasir Pengaraian (UPP). The data from this study were collected through tests. The test questions given relate to communication ability. The sample of this research was prospective mathematics teacher students who contracted the Structure Algebra course at UIR (experimental class) and prospective mathematics teacher students at UPP (control class) in the 2021/2022 academic year. The data collection method used is a mathematical communication ability test and a statistical test processes the test result data. Normality test using Kolmogorov-Smirnov and homogeneity test using Levene and the T-test. Based on the T-test result, a significance value of 0.016 < 0.05 was obtained. It means that there is an increase in the mathematical communication ability of a student who receives learning using interactive multimedia-based teaching material.